PELUKAN KASIH: PERAN ORANG TUA DALAM MENDUKUNG TUMBUH KEMBANG ANAK BERKEBUTUHAN KHUSUS - Cahyaningrat, Dewi (LPPM Universitas Bina Bangsa, 2025)
This study aims to explore the role of parents in supporting the growth and development of children with special needs (ABK) through emotional, educational, and social approaches. Children with special needs require extra attention and support in various aspects of their lives. Parents play an important role in providing a safe environment, consistent affection, and supporting the child's learning process. This study used a qualitative descriptive method, involving 10 parents of children with special needs as participants. The results showed that parental support plays a significant role in improving children's emotional well-being, cognitive development, and social skills. Despite challenges such as social stigma and fatigue, active parental involvement helps children overcome various developmental barriers. This study highlights the importance of loving emotional support, collaboration with professionals, and the role of parents in building children's social skills. Thus, the embrace of parental affection is a key factor in facilitating the optimal growth and development of children with special needs.